Decreased muscle‐derived musclin by chronic resistance exercise is associated with improved insulin resistance in rats with type 2 diabetes. Issue 9 (5th May 2021) - Shimomura, Mio; Horii, Naoki; Fujie, Shumpei; Inoue, Kenichiro; Hasegawa, Natsuki; Iemitsu, Keiko; Uchida, Masataka; Iemitsu, Motoyuki
Abstract: Chronic resistance exercise induces improved hyperglycemia in patients with type 2 diabetes mellitus. Musclin, a muscle‐derived secretory factor, is involved in the induction of insulin resistance via the downregulation of the glucose transporter‐4 (GLUT‐4) signaling pathway in skeletal muscles. However, whether musclin affects the mechanism of resistance exercise remains unclear. This study aimed to clarify whether decreased muscle‐derived musclin secretion in chronic resistance exercise is involved in the improvement of insulin resistance via the GLUT‐4 signaling pathway in rats with type 2 diabetes. Male, 20‐week‐old, Otsuka Long‐Evans Tokushima Fatty (OLETF) rats, a type 2 diabetes model, were randomly divided into two groups: sedentary control (OLETF‐Con) and chronic resistance exercise (OLETF‐RT; climbing a ladder three times a week on alternate days for 8 weeks), whereas Long‐Evans Tokushima Otsuka rats were used as the nondiabetic sedentary control group. OLETF‐Con rats showed increased fasting glucose levels, decreased insulin sensitivity index (QUICKI), muscle GLUT‐4 translocation, and protein kinase B (Akt) phosphorylation, and concomitantly increased muscle musclin expression. In contrast, OLETF‐RT rats significantly reduced muscle musclin expression, improved hyperglycemia, and QUICKI through an accelerated muscle GLUT‐4/Akt signaling pathway. Moreover, chronic resistance exercise‐induced reduction of muscle musclin was correlated with changes in fasting glucose, QUICKI, GLUT‐4 translocation, and Akt phosphorylation. These findings suggest that the reduction in muscle‐derived musclin production by chronic resistance exercise may be involved in improved insulin resistance in rats with type 2 diabetes. Abstract : 8‐week resistance exercise significantly reduced musclin protein levels in the skeletal muscle of rats with type 2 diabetes. Importantly, chronic resistance exercise‐induced reduction of musclin protein levels in the skeletal muscle were significantly associated with activation of muscle Akt phosphorylation and GLUT4 translocation. These results suggest that the chronic resistance exercise‐induced reduction of musclin is involved in the improvement of hyperglycemia and insulin resistance via the activation of the muscle Akt/GLUT4 signaling pathway in rats with type 2 diabetes. ​